2008
DOI: 10.1091/mbc.e07-11-1203
|View full text |Cite
|
Sign up to set email alerts
|

Signal-dependent Regulation of Transcription by Histone Deacetylase 7 Involves Recruitment to Promyelocytic Leukemia Protein Nuclear Bodies

Abstract: Promyelocytic leukemia protein (PML) nuclear bodies (NBs) are dynamic subnuclear compartments that play roles in several cellular processes, including apoptosis, transcriptional regulation, and DNA repair. Histone deacetylase (HDAC) 7 is a potent corepressor that inhibits transcription by myocyte enhancer factor 2 (MEF2) transcription factors. We show here that endogenous HDAC7 and PML interact and partially colocalize in PML NBs. Tumor necrosis factor (TNF)-alpha treatment recruits HDAC7 to PML NBs and enhanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
46
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(48 citation statements)
references
References 33 publications
(18 reference statements)
2
46
0
Order By: Relevance
“…(C) Telomerase activity of the PML-IV-stable cell lines. The extracts of H1299, mock, or stable cell lines were tested for telomerase activity as described in recruit several proteins, including CBP, p53, Hdm2 (MDM2), PIN1, HDAC7 and HCMV IE1, suggesting that unSUMOylated primary PML-NBs still have an important biological function (Bischof et al, 2002;Gao et al, 2008;Kang et al, 2006;Lallemand-Breitenbach et al, 2001;Reineke et al, 2008;Wei et al, 2003). Indeed, SUMOylation of PML is dispensable for premature senescence induced by p53, because PML3M can induce growth arrest and senescence (Bischof et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…(C) Telomerase activity of the PML-IV-stable cell lines. The extracts of H1299, mock, or stable cell lines were tested for telomerase activity as described in recruit several proteins, including CBP, p53, Hdm2 (MDM2), PIN1, HDAC7 and HCMV IE1, suggesting that unSUMOylated primary PML-NBs still have an important biological function (Bischof et al, 2002;Gao et al, 2008;Kang et al, 2006;Lallemand-Breitenbach et al, 2001;Reineke et al, 2008;Wei et al, 2003). Indeed, SUMOylation of PML is dispensable for premature senescence induced by p53, because PML3M can induce growth arrest and senescence (Bischof et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Transient transfections and luciferase assays were performed in 48-well culture plates according to our previously published protocol (22). HeLa cells were transfected with an muscle creatine kinase (MCK) promoter-containing reporter construct and CMX-␤-galactosidase (CMX-␤-Gal) expression plasmids.…”
Section: Methodsmentioning
confidence: 99%
“…Indirect immunofluorescence microscopy was conducted according to our published protocol (22). The cells were plated onto coverslips of 12-well plates and transfected using Lipofectamine 2000 (Invitrogen) according to the manufacturer's protocol.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Viral infection also results in degradation of PML protein and disruption of the PML NBs (26,27). We have previously demonstrated that tumor necrosis factor ␣ (TNF␣) significantly induces PML accumulation in human umbilical vascular endothelial cells (28) and that HDAC7 is critical for TNF␣-induced NB formation by modulating PML SUMOylation (29). We also reported that PML interacts with the peptidyl-prolyl cis-trans isomerase, Pin1, in a phosphorylation-dependent manner and that this interaction promotes PML degradation (30).…”
mentioning
confidence: 99%